Chemistry and toxicology of pollution : ecological and human health - Connell, D. W.; Miller, Gregory J. (Hoboken: Wiley, 2022)
"The Second Edition of Chemistry and Toxicology of Pollution is an update and major expansion, now covering the effects of chemical pollution on human health. The human health impacts of pollutants can be considered together with the ecosystem impacts, since the study of both have similar approaches. In addition, much can be gained by understanding the similarities and differences of the impact of pollutants on the natural environment and humans. This edition contains a comprehensive update of the content of the Chemistry and Ecotoxicology of Pollution, with the addition of integrated material on human toxicology, and new chapters covering topics relevant to current pollution issues such as global warming and climate change effects. Theory and practice within chapters are strongly supported by scientific literature that reflects the global and regional nature of pollution and ecological effects, with an emphasis on North America, UK, Europe, China, India and Australia. This major updated approach also covers recent advances in environmental science, monitoring and assessment of new and emerging pollutants, risk assessment, remediation and sustainable management of pollution effects on ecosystems and human health"--
Includes bibliographical references and index.
Keywords: Pollution; Environmental toxicology